Iron state and hepatic disease in patients with thalassaemia major, treated with long term subcutaneous desferrioxamine. Issue 11 (November 1987) - Aldouri, M A; Wonke, B; Hoffbrand, A V; Flynn, D M; Laulicht, M; Fenton, L A; Scheuer, P J; Kibbler, C C; Allwood, C A; Brown, D
Abstract : Liver biopsies were performed on 51 regularly transfused patients with beta thalassaemia, age range 5-36 (mean 18.6) years, who had received regular subcutaneous desferrioxamine (DFX) treatment for periods between one and eight years (40 for eight years). The biopsy specimens were examined by light microscopy and immunofluorescence for hepatitis B virus surface and core antigens (HBsAg and HBcAg), and the iron content was determined chemically. The results were compared with serum ferritin concentration and aspartate transaminase (AST) activity and with hepatitis B virus serology. Biopsy specimens, in which chemical liver iron had been determined in 12, were also available from 17 patients. Mean serum ferritin (+/- SD) had fallen from 5885 (3245) micrograms/l to 1638 (976) micrograms/l in 36 patients after eight years' chelation, while mean (+/- SD) liver iron concentration had fallen from 2945 (900) micrograms/100 mg dry weight to 857 (435) micrograms/100 mg dry weight in 12 of them. All biopsy specimens examined were negative for HBs and HBc antigens. The presence of histological features of hepatitis was associated with increased liver iron content, increased fibrosis, and with progression of fibrosis between the two biopsies. Procollagen III peptide was assayed in 28 patients but did not correlate with the degree of hepatitis, fibrosis, or with chemical liver iron content. We conclude that with regular subcutaneous DFX, mean concentrations of serum ferritin and liver iron are maintained in these patients at about five and 10 times the normal value, respectively, and that progression of liver damage is more likely to be due to viral hepatitis, presumably related to the parenterally transmitted non-A, non-B agents than to iron overload.